Profitabilitas Pada Bank Umum Swasta Nasional Devisa di Bursa Efek Indonesia - Dinarossi Utami (LPPM Universitas Lembah Dempo, 2019)
This study aimed to determine the effects of internal and external factors on profitability in National Private Foreign-Exchange Bank listed on the Indonesia Stock Exchange (BEI). The type of research used the type of associative research. The data in this study used secondary data obtained from the official website of BEI (www.idx.co.id). Data collection method in this research used documentation method. Data analysis in this research used quantitative analysis. The analysis technique used multiple regression analysis with the help of SPSS 16.0 application. The result of the analysis showed partially Operational Cost Operating Income had a significant negative effect on probability, Loan to Deposit Ratio had no effect on profitability, Capital Adequacy Ratio had effect profitability, Third Party Fund had no effect on profitability, Credit had no effect on profitability and Non Performing Loan had effect on profitability. Simultaneously Operational Revenue Operating Expenses, Loan to Deposit Ratio, Capital Adequacy Ratio, Third Party Funds, Credit and Non Performing Loan effect on Profitability at National Private Foreign-Exchange Bank registered on the Stock Exchange.